Enhancing the sustainability of the aviation industry: Airlines' commitment to "green" practices - Vera Amicarelli; Giovanni Lagioia; Antonio Patruno; Raluca Mariana Grosu; Christian Bux (Amfiteatru Economic Journal, 2021)
The aviation industry represents an important polluter, being responsible for increasing environmental impacts on global scale. Aiming to approach the adoption of suitable policies in the aviation industry towards the achievement of the national and international sustainability goals, the present research tackles airlines' commitment to aviation-related environmental issues, as well as their willingness to adopt sustainable aviation fuel (i.e., bio jet fuel) and sustainable development strategies, focusing on those companies operating flights in the Karol Wojtyła Airport (Bari, Italy). The paper adopts the χ2 test and the logistic regression to investigate three different hypotheses related to airlines' headquarters, carriers' typology (i.e., low-cost or not, flag carriers or not) and years of service. Results outline that traditional airlines, either flag carriers or not, as well as South and North American companies, are more likely to be aware of aviation environmental consequences, publishing environmental reports and offering to passengers the chance to participate to climate change reduction (e.g., through online carbon offset programs or more expensive ticket to produce bio jet fuels). In addition, airlines transiting in Karol Wojty±a Airport show a small willingness to share information through environmental reports and are scarcely intentioned to make use of bio jet fuels, confirming that low-cost companies are still less attentive towards aviation environmental issues. The present research contributes to the empirical studies on sustainable aviation and carriers' commitment to environmental strategies, highlighting the need to enhance carbon offsets programs and digital technologies as the online compensation of CO2 emissions.
Keywords: Q01; Q5; Q56; 330; sustainability; sustainable tourism; aviation; environmental protection; airlines' commitment; bio jet fuels